Ischemic maculopathy in zidovudine-induced anemia in an HIV-positive man - Kathir Yoganathan (Dove Medical Press, 2008)
Kathir Yoganathan1, Michael Austin21Department of Genito-Urinary Medicine, 2Department of Ophthalmology, Singleton Hospital, Sketty, Swansea, SA2 8QA, UKAbstract: Opportunistic cytomegalovirus (CMV) infection is common in severely immunocompromised HIV-positive patients. The retina is the commonest site of involvement with hemorrhages a prominent feature. CMV retinitis affects 40% of HIV positive patients who have CD4 count of less than 100 cell/mm3, and in these circumstances clinicians are likely to consider commencing anti-CMV therapy without considering other causes. We report a man with HIV who developed bilateral retinal hemorrhages and ischemic maculopathy in association with zidovudine (AZT)-induced anemia. Retinal hemorrhages resolved following blood transfusion.Keywords: Ischemic maculopathy, retinal hemorrhages, anemia, zidovudine, HIV